PENGARUH FAKTOR GEOGRAFIS TERHADAP POTENSI GAGAL PANEN JAGUNG DI KECAMATAN INSANA TENGAH KABUPATEN TIMOR TENGAH UTARA TAHUN 2020 - Mnou, Maria Carmelita; Wulakada, Hamza Huri; Sukmawati, Sukmawati (Universitas Nusa Cendana, 2023)
In 2020 corn production in TTU Regency experienced a decrease in corn productivity by 21.91 percent from 2019 corn production of 46,621 tons to 36,406, one of which is Central Insana District. This study aims to: (1) Identify the geographical and non-geographical factors that influence the potential for maize crop failure in Insana Tengah Subdistrict, (2) Identify the efforts made by the people of Insana Tengah in dealing with maize crop failure. This research is a quantitative research with descriptive method with variable X in the form of geographical factors namely rainfall, sunshine, slope while variable Y is potential corn crop failure. The study population was 895 farmers with a sample of 90 farmers from 7 villages in Insana Tengah sub-district determined using the Slovin formula with an error rate of 10%. Data sources consisted of primary and secondary data collected by observation, documentation, and questionnaires. The analysis method uses descriptive analysis, multiple correlation, with Microsoft Excel, and SPSS software. The results showed that: (1) Geographical factors in the form of slope have a higher influence than the intensity of rainfall, the intensity of solar irradiation, has an influence of 0.638 while, the intensity of rainfall, the intensity of solar irradiation 0.287 and 0.294. (2) Efforts made by the community are in the form of non-geographical factors, in dealing with pest attacks on corn plants the community does by means of technical culture control, namely by managing planting media, cleaning weeds, and providing fertilizers that are not excessive. Then chemical control is done by using active insecticides. Based on the results of the study, it is concluded that geographical factors in the form of rainfall intensity, sunlight intensity, and slope have an influence on corn crop failure. The influence of geographical factors in the form of rainfall intensity, sunlight intensity, and slope on corn crop failure in Insana Tengah Subdistrict using multiple correlation analysis obtained a result of 0.759 which shows that the factors of rainfall intensity, sunlight intensity, and slope, have an influence of 76% on corn crop failure, while 24% is influenced by other factors.